Answer:
Solving the given expression
we get 0=0
Explanation:
We need to solve the expression:
![x+(1)/(2)-x=(1)/(2)](https://img.qammunity.org/2022/formulas/mathematics/high-school/gxby42efzrpkn9ylwve237fi99bqzr31ig.png)
Solving the expression:
We will use simple maths rules to solve the expression
![x+(1)/(2)-x=(1)/(2)](https://img.qammunity.org/2022/formulas/mathematics/high-school/gxby42efzrpkn9ylwve237fi99bqzr31ig.png)
Subtracting 1/2 on both sides and simplify
![x+(1)/(2)-x-(1)/(2)=(1)/(2)-(1)/(2)\\x-x=0\\0=0](https://img.qammunity.org/2022/formulas/mathematics/high-school/7zv3enw1dim9qmf7gotoo2yrr0fzbs99pc.png)
Solving the given expression
we get 0=0
So, the expression is true for all values of x. there will be infinite solutions to the system.